THE PRE-TRIAL APPLICATION GRANTED IN THE CASE OF BUDI GUNAWAN - Saputra, Cokky Wijaya (Lembaga Penelitian dan Pengabdian Masyarakat, 2019)
This study tries to analyze cases that have been experienced by prospective police chief Budi Gunawan (BG) on the application of pre-trial which was considered odd in the event of violations in the verdict given by Sarpin Rizal as chairman of the court. This resulted in the KPK not being able to submit another legal effort to sue again, because the pretrial decision was final and binding on a lawsuit case. The analysis method used in this study is a qualitative research method in which data analysis is carried out in a descriptive manner that refers to a particular problem and is associated with existing legislation, namely: 1) The 1945 Constitution of the Republic of Indonesia; 2) Law No. 8 of 1981 concerning Criminal Procedure Law (KUHAP); 3) Law Number 48 of 2009 concerning judicial authority. The collection of legal materials is done by library research. Judge Sarpin Rizaldi's decision reaped many irregularities. The irregularity lies in the decision that does not pay attention to the existence of pretrial as stipulated in the Criminal Procedure Code and legislation relating to corruption.